The Development of Website-based Learning Management System (LMS) as A Tool for Learning in the Covid-19 Pandemic Period for Junior High Schools - Sumardi, Dody; Suryani, Nunuk; Musadad, Akhmad Arif (Journal of Education Technology, 2021)
The impact of the COVID-19 pandemic requires the world of education to continue learning so that the learning process can run well through the use of web-based information and communication technology (ICT) in the learning management system (LMS) format. Therefore, this research and development aims to develop a Website-based Learning Management System to facilitate learning during the covid-19 pandemic. This research is included in the type of research and development (R&D) by adopting the Alessi & Trollip development model. The subject of this research is two media experts, two material experts, and two subject teachers of Junior Highs School. The data collection technique used a test based on the product developed by each research subject using the appropriate instrument. The results of the questionnaire will be analyzed descriptively using percentages to decide the feasibility of the LMS product[R1]Â . From this research, it showed that the assessment of media experts was 88.88%, the total averagesr was 91.22% and prospective users consisting of students and teachers were 91.88%, which means that the acquisition of the media and subject matter to be used is above 81%, which is included in the very decent or very good category so there is no need for revision or improvement. Thus the learning application, namely the learning management system (LMS) can be used as a tool to support the online learning processÂ [R1]The data analysis technique